Trace Element (Fe, Co, Ni and Cu) Dynamics Across the Salinity Gradient in Arctic and Antarctic Glacier Fjords - Krause, Jana; Hopwood, Mark J.; Höfer, Juan; Krisch, Stephan; Achterberg, Eric P.; Alarcón, Emilio; Carroll, Dustin; González, Humberto E.; Juul-Pedersen, Thomas; Liu, Te; Lodeiro, Pablo; Meire, Lorenz; et al. (Frontiers in Earth Science, 2021)
Around the Greenlandic and Antarctic coastlines, sediment plumes associated with glaciers are significant sources of lithogenic material to the ocean. These plumes contain elevated concentrations of a range of trace metals, especially in particle bound phases, but it is not clear how these particles affect dissolved (<0.2 µm) metal distributions in the ocean. Here we show, using transects in 8 glacier fjords, trends in the distribution of dissolved iron, cobalt, nickel and copper (dFe, dCo, dNi, dCu). Following rapid dFe loss close to glacier outflows, dFe concentrations in particular showed strong similarities between different fjords. Similar dFe concentrations were also observed between seasons/years when Nuup Kangerlua (SW Greenland) was revisited in spring, mid- and late-summer. Dissolved Cu, dCo and dNi concentrations were more variable and showed different gradients with salinity depending on the fjord, season and year. The lack of consistent trends for dCu and dNi largely reflects less pronounced differences contrasting the concentration of inflowing shelf waters with fresher glacially-modified waters. Particles also made only small contributions to total dissolvable Cu (dCu constituted 83 ± 28% of total dissolvable Cu) and Ni (dNi constituted 86 ± 28% of total dissolvable Ni) within glacier plumes. For comparison, dFe was a lower fraction of total dissolvable Fe; 3.5 ± 4.8%. High concentrations of total dissolvable Fe in some inner-fjord environments, up to 77 µM in Ameralik (SW Greenland), may drive enhanced removal of scavenged type elements, such as Co. Further variability may have been driven by local bedrock mineralogy, which could explain high concentrations of dNi (25–29 nM) and dCo (6–7 nM) in one coastal region of west Greenland (Kangaatsiaq). Our results suggest that dissolved trace element distributions in glacier fjords are influenced by a range of factors including: freshwater concentrations, local geology, drawdown by scavenging and primary production, saline inflow, and sediment dynamics. Considering the lack of apparent seasonality in dFe concentrations, we suggest that fluxes of some trace elements may scale proportionately to fjord overturning rather than directly to freshwater discharge flux.